2009
DOI: 10.1111/j.1468-2958.2008.01339.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Workers and HIV/AIDS: Analyzing Participatory Culture-Centered Health Communication Strategies

Abstract: An emerging trend in health communication research advocates the need to foreground articulations of health by participants who are at the core of any health campaign. Scholarly work suggests that the culture-centered approach to health communication can provide a theoretical and practical framework to achieve this objective. The culture-centered approach calls for attention to dialogue and locates the agency of cultural participants in the culture being studied. This approach underlines the import of particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…Without the agency control of this one individual, sex workers in India would have purportedly descended to Africa-scale pandemic status. The excerpt provides no agency to the sex workers in determining their own health outcomes, which is an interesting move, given the fact that literature on HIV/AIDS efforts among Indian sex worker communities has shown that some of the most effective efforts have been the ones in which the members of the communities themselves have played an active role in their own education and prevention (Basu & Dutta, 2009). The native body is accorded no subjectivity or agency; it becomes a body that needs constant control from the Western scientific enterprise.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Without the agency control of this one individual, sex workers in India would have purportedly descended to Africa-scale pandemic status. The excerpt provides no agency to the sex workers in determining their own health outcomes, which is an interesting move, given the fact that literature on HIV/AIDS efforts among Indian sex worker communities has shown that some of the most effective efforts have been the ones in which the members of the communities themselves have played an active role in their own education and prevention (Basu & Dutta, 2009). The native body is accorded no subjectivity or agency; it becomes a body that needs constant control from the Western scientific enterprise.…”
Section: Methodsmentioning
confidence: 98%
“…In the case of the HIV/AIDS pandemic, the meanings of the disease intersect with the articulation of health policies, the implementation of such policies, and the development of interventions attached to those meanings (Airhihenbuwa & Obregon, 2000). With reference to theorizing and scholarship in health communication, a postcolonial approach draws attention to the unequal terrain of disciplinary knowledge in health communication that has been dominated by primarily United States-based and, to some extent, Europe-based perspectives (Basu & Dutta, 2009;Dutta, 2008a;Dutta-Bergman, 2004a). Further, the deconstructive move in the postcolonial approach creates openings for disciplinary transformations through the interrogation of the taken-for-granted assumptions in West-centric productions of knowledge (Dutta, 2008).…”
Section: Postcolonial Theory and Hiv/aidsmentioning
confidence: 99%
“…It foregrounds those marginalized communication patterns and scripts that are hidden from mainstream discourse and formulates a theoretical paradigm that aims to create openings for the inclusion of subaltern voices. Extended to the realm of health communication, Subaltern Studies forges entry points for listening to the histories and the voices of subalterns as they script their localized vocabularies on health, illness, and suffering (Basu & Dutta, 2009Dutta-Bergman, 2004a). These localized vocabularies constitute what Bhadra (1997) terms an autonomous subaltern consciousness.…”
Section: Subaltern Consciousness and Healthmentioning
confidence: 98%
“…Theoretically positioned within the framework of the Subaltern Studies project (Beverly, 2004;Guha & Spivak, 1988;Spivak, 1988), the aim of this paper is to locate a subaltern consciousness at the heart of theorizing and practice regarding HIV/AIDS communication in sex worker spaces. Only a handful of studies in communication, specifically in health communication (see Basu & Dutta, 2008, 2009Dutta-Bergman, 2004a, b), are based on the Subaltern Studies framework, and this is the first empirical project to theorize communication, as a meaningmaking endeavor, from the standpoint of a foundational concept that straddles the Subaltern Studies project. Specifically, this paper uses ethnographic data to explain how an autonomous subaltern rationality influences and is vital to understanding the processes and outcomes of sense-making on health and HIV/AIDS in a sex worker community in the global south.…”
Section: Sex Work and Hiv/aids Campaignsmentioning
confidence: 99%
“…From such a perspective, issues of voice and identity as they play out in subaltern contexts are problematized, and taken-for-granted dominant ideological assumptions about a subaltern's lack of ability to speak and act for her or his good are challenged (Basu & Dutta, 2009). The culture-centered perspective argues that the subaltern, indeed, can speak, but that the subaltern's voice typically is not recognized as legitimate by mainstream knowledge frameworks.…”
Section: The Culture-centered Approach To Health Communicationmentioning
confidence: 98%